1981
DOI: 10.2355/isijinternational1966.21.326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neutron and Electron Irradiation on Low Manganese Steels

Abstract: SynopsisThe interaction between solute atoms and radiation induced defects was studied by means of tensile test and transmission electron microscopy. The defects were produced by neutron irradiation at 473 K to a fluence of 6.4 x 1022 of m2 (E n> 1 MeV) and electron irradiation at 650 kV electron microscope to a fluence of 7 x 1025 of m2.Radiation hardening and radiation embrittlement occurred by neutron irradiation. The yield stress increased and the total elongation decreased with the increase of manganese c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 3 publications
0
18
1
Order By: Relevance
“…The reference experimental data are denoted with triangles [4]. Included in the graph are also data from other comparable irradiation experiments in Fe-C (bullets) [9,8,10,11,12,13]. See [6] for full details.…”
Section: Simulation Of the Nanostructure Evolution During Isochronal ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The reference experimental data are denoted with triangles [4]. Included in the graph are also data from other comparable irradiation experiments in Fe-C (bullets) [9,8,10,11,12,13]. See [6] for full details.…”
Section: Simulation Of the Nanostructure Evolution During Isochronal ...mentioning
confidence: 99%
“…To get a more complete picture from the available experimental data in α-Fe, we have also considered other experiments, with less complete data: [9,10,11,12,13]. A more thorough overview of the available irradiation and annealing experiments with pure Fe will be published in a separate paper [6].…”
Section: Introductionmentioning
confidence: 99%
“…(5). The computed value of a suggests a higher obstacle strength for h1 0 0i loops than other calculations quoted in the literature [22,39]. Of course, N and d have been obtained directly from our computation box and are subject to the narrow applicability window of this MD simulation.…”
Section: Estimation Of the Hardeningmentioning
confidence: 96%
“…Although it is difficult to reveal the nature of point defect clusters less than 1 nm by transmission electron microscopy (TEM), vacancy clusters can be pursued by positron annihilation spectroscopy (PAS). However, only a few studies have reported the irradiation hardening and microstructure changes in Fe-Mn alloys [14,15]. Furthermore, the irradiation dose that the materials used in previous studies were subjected to was so low that the effect of Mn probably could not form a sufficient number of point defect clusters.…”
Section: Introductionmentioning
confidence: 99%